Comparative liquid chromatography/tandem mass spectrometry lipidomics analysis of macaque heart tissue flash‐frozen or embedded in optimal cutting temperature polymer (OCT): Practical considerations. (16th July 2021) - Vaswani, Ashish; Alcazar Magana, Armando; Zimmermann, Eric; Hasan, Wohaib; Raman, Jaishankar; Maier, Claudia S.
Abstract : Rationale: Biobanks of patient tissues have emerged as essential resources in biomedical research. Optimal cutting temperature compound (OCT) blends have shown to provide stability to the embedded tissue and are compatible with spectroscopic methods, such as infrared (IR) and Raman spectroscopy. Data derived from omics‐methods are only useful if tissue damage caused by storage in OCT blends is minimal and well understood. In this context, we investigated the suitability of OCT storage for heart tissue destined for liquid chromatography/tandem mass spectrometry (LC/MS/MS) lipidomic studies. Methods: To determine the compatibility of OCT storage with LC/MS/MS lipidomics studies. The lipid profiles of macaque heart tissue snap‐frozen in liquid nitrogen or stored in an OCT blend were evaluated. Results: We have evaluated a lipid extraction protocol suitable for OCT‐embedded tissue that is compatible with LC/MS/MS. We annotated and evaluated the profiles of 306 lipid species from tissues stored in OCT or liquid nitrogen. For most of the lipid species (95.4%), the profiles were independent of the storage conditions. However, 4.6% of the lipid species; mainly plasmalogens, were affected by the storage method. Conclusions: This study shows that OCT storage is compatible with LC–MS/MS lipidomics of heart tissue, facilitating the use of biobanked tissue samples for future studies.